Kinematic analysis of soccer goalkeepers' diving motion towards shots placed far away - Numazu, N.; Fujii, N.; Koido, M. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
The purpose of this study was to clarify the biomechanical characteristics of soccer goalkeepers (GKs) diving for shots placed distantly from the GK. Fifteen collegiate male GKs and 13 collegiate male outfield players acting as strikers participated. The experimental situation involved shooting from inside the penalty area. The strikers were instructed to execute an instep kick placing the ball 16.5 m away from the GK after pushing the ball forward. The GKs were instructed to dive with a preparatory motion toward the shot ball. Three-dimensional coordinate data for the strikers and GKs were captured using 2 motion capture systems - one with 16 cameras for the GKs and the other with 8 cameras for the strikers (250Hz). The systems were synchronized with an analog signal via an A/D converter (1000 Hz) and input to a computer. The shooting areas were divided into 12 (i.e. 2 shooting directions to the right and left sides of the GKs, 2 shooting distances close to and far from the GKs, and 3 shot heights, close to the ground, and also at high and medium heights). The strikers were informed of the target shooting area randomly in each trial, and 213 trials in which the GKs dived toward shots placed in the far area were selected. We calculated the velocity of the center of gravity and the joint angles of the lower limbs. The major findings were as follows. 1) Regardless of shooting height, it appeared that the GKs performed almost the same motion until landing because they began to move after determining the diving direction. 2) In order to dive to lower-placed balls, leaning the trunk towards the diving direction was necessary to allow placement of the hand in the lower position. 3) Regardless of shooting height, the side contralateral (CS) to the leg in the diving direction had the same role of achieving movement of the center of gravity in the diving direction. 4) The GKs dived toward lower-placed shots by flexing the knee joint of their CS leg and the hip and knee joints of their ball side (BS) leg before the BS leg touched the ground. 5) The GKs dived towards individual shot heights by appropriately adjusting the posture of their BS leg before the BS leg touched the ground.